The Efficacy of Bioagents against Post Flowering Stalk Rot (PFSR) of Specialty Corn Caused by Fusarium verticillioides (sheldon) - Jat, Anita; Sharma, S. S.; Dhakar, Hansraj (International Journal of Bio-resource and Stress Management, 2018)
The efficacy of three bio-agents viz. Pratap Trichoderma viride-1, Trichoderma viride and Trichoderma harzianum were assessed in vitro against four isolates (Fv SC-01, Fv SC- 02, Fv SC-03 and Fv SC- 04) of Fusarium verticillioides, cause Post flowering stalk rot (PFSR) ofspecialty corn. All used bio- agents were antagonistic in nature and significantly inhibited the growth of Fusarium verticillioides. Among the bio-agents tested maximum inhibition of mycelium growth was observed by Pratap Trichoderma viride-1 @ 1500 ppm on Fv SC-04.Out of these antagonists, the resident isolate Pratap Trichoderma viride -1(78.45%) provided the highest inhibitory effect followed by Trichoderma viride (78.22%) and Trichoderma harzianum (56.60%) was the lowest suppressive antagonist. Among all isolates of Fusarium verticillioides Fv SC-04 was maximum inhibited by all tested bio- agents.